Hydration status and blood pressure variability in primary hypertensive patients - Oguzhan Sıtkı Dizdar; Ali Yeşiltepe; Engin Dondurmaci; Eyup Ozkan; Ali Koç; Ali Ihsan Gunal (Nefrología (English Edition), 2020)
Background: Increased blood pressure variability (BPV) is associated with higher cardiovascular risk. The association between BPV and fluid status in hypertensive patients has not been investigated so far. The aim of the present study was to determine the contribution of fluid balance to BPV and impact on endothelial and cardiac functions among primary hypertensive patients. Methods: This is a prospective interventional study conducted in primary hypertensive patients with one-year follow-up. Volume status measurements by a body composition monitor, ambulatory blood pressure (BP) monitoring, echocardiographic and carotid intima-media thickness (CIMT) measurements were performed at enrollment and at twelfth. Patients in one of the two groups were kept negative hydrated during trial with diuretic treatment. Patients in other group were positively hydrated (hypervolemic) at enrollment, antihypertensive drugs other than diuretics (vasodilator agents) were added or intensified according to the BP monitoring. Average real variability (ARV) index was used for establishing the prognostic significance of BPV. Results: The study population consisted of 50 patients with a mean age of 54.5 ± 8.8 years. At the end of one-year follow-up, patients in negative hydrated group were found to have significantly lower BP, CIMT, left ventricle mass index (LVMI) and systolic and diastolic ARV. More weight gain and higher systolic BP were major risk factors of high systolic ARV. Patients who have improvement in CIMT and LVMI were considered as target organ damage (TOD) recovery present. In negatively hydrated group, TOD significantly reduced during trial. In patients who have TOD recovery, BPV significantly more reduced like systolic and diastolic BP. Significant risk factors associated with the presence of TOD were 24 h systolic BP and daytime and night time diastolic ARV and night time diastolic BP. Conclusion: Addition of diuretic to established treatment or intensified diuretic treatment and keeping patients in negative hydration status resulted in reduction in BPV at twelfth month of follow-up. More weight gain and higher systolic BP are major risk factors of high systolic ARV, but not hypervolemia. BPV, especially diastolic ARV, was significantly associated with TOD. Resumen: Antecedentes: El aumento en la variabilidad en la presión arterial (VPA) se asocia con un mayor riesgo cardiovascular. Hasta el momento no se ha investigado la asociación entre la VPA y el estado hidroelectrolítico en pacientes hipertensos. El objetivo del presente estudio fue determinar la contribución del equilibrio hidroelectrolítico a la VPA y el impacto en las funciones endoteliales y cardíacas entre los pacientes con hipertensión primaria. Métodos: Se trata de un estudio intervencionista prospectivo realizado en pacientes con hipertensión primaria con seguimiento de un año. Se llevaron a cabo mediciones del estado volumétrico mediante un monitor de composición corporal, monitorización de presión arterial (PA) ambulatoria, mediciones ecocardiográficas y del grosor de la íntima-media de la carótida (GIMC) en la inclusión y en el duodécimo mes. En los pacientes de uno de los 2 grupos se mantuvo hidratación negativa durante el ensayo con tratamiento diurético. Los pacientes de otro grupo presentaban hidratación positiva (hipervolemia) en la inclusión, y se añadieron o se intensificaron los fármacos antihipertensivos distintos de los diuréticos (vasodilatadores) en función de la monitorización de la PA. Se utilizó el índice de variabilidad real promedio (VRP) para establecer la significación pronóstica de la VPA. Resultados: La población del estudio consistió en 50 pacientes con una media de edad de 54,5 ± 8,8 años. Al final del seguimiento, al cabo de un año, los pacientes del grupo con hidratación negativa presentaron una PA, un GIMC, un índice de masa del ventrículo izquierdo (IMVI) y una VRP sistólica y diastólica significativamente menores. El mayor aumento de peso y una PA sistólica superior fueron factores de riesgo importantes de la VRP sistólica alta. Los pacientes con mejoras en el GIMC y el IMVI se consideraron pacientes con recuperación del daño de órganos diana (DOD). En el grupo con hidratación negativa, el DOD se redujo significativamente durante el ensayo. En los pacientes con recuperación del DOD, la VPA se redujo significativamente en mayor medida, al igual que la PA sistólica y diastólica. Los factores de riesgo significativos asociados con la presencia de DOC fueron la PA sistólica de 24 h, la VPA diastólica diurna y nocturna y la PA diastólica nocturna. Conclusión: La adición de diuréticos al tratamiento establecido o la intensificación del tratamiento diurético y el mantenimiento de los pacientes en estado de hidratación negativa provocó la reducción de la VPA en el duodécimo mes de seguimiento. El mayor aumento de peso y una PA sistólica superior son factores de riesgo importantes de VRP sistólica alta, pero no así la hipervolemia. La VPA, en especial la VPA diastólica se asoció de forma significativa al DOD.